2016
DOI: 10.1136/bjsports-2016-096142
|View full text |Cite
|
Sign up to set email alerts
|

Does sports participation (including level of performance and previous injury) increase risk of osteoarthritis? A systematic review and meta-analysis

Abstract: BackgroundTo assess the relationship between sport and osteoarthritis (OA), and specifically to determine whether previous participation, in terms of level (elite or non-elite), type of sport, intensity or previous injury, was associated with OA.MethodsThis systematic review was developed using PRISMA guidelines. Databases were searched (to May 2016). Narrative review and meta-analysis (with risk ratio (RR) and 95% CIs) approaches were undertaken where appropriate. Study quality was assessed using GRADE.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 64 publications
1
43
0
4
Order By: Relevance
“…The prevalence of CC was significantly higher in ex-footballers (24.3%) compared with the general population (8.8%) and previous population estimates (7%–10%). 29 Both KOA and prior joint insult are recognised risk factors for CC, 11 so this increased prevalence is consistent with more biomechanical knee trauma in footballers. Furthermore, concurrence of CC with KOA may associate with greater clinical severity and worse outcomes.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The prevalence of CC was significantly higher in ex-footballers (24.3%) compared with the general population (8.8%) and previous population estimates (7%–10%). 29 Both KOA and prior joint insult are recognised risk factors for CC, 11 so this increased prevalence is consistent with more biomechanical knee trauma in footballers. Furthermore, concurrence of CC with KOA may associate with greater clinical severity and worse outcomes.…”
Section: Discussionmentioning
confidence: 82%
“… 2 Indeed, a recent systematic review cited the same limitations and concluded that only ‘very low quality’ evidence suggests football increases the risk of KOA. 11 No studies have used a general population group for comparison, so whether ex-footballers have more KOA than the general population remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Im Bereich der unteren Extremität besteht ein erhöhtes Risiko für Arthrosen im Knie-und Hüftgelenk in Kraftsportarten sowie in Sportarten mit schnellen Richtungswechseln [36]. Beispielsweise zeigt sich im Fußball, nicht jedoch im Laufsport, ein erhöhtes Risiko für Arthrose bei Elitesportlern im Vergleich zu Nichtelitesportlern [42]. Höheres Körpergewicht scheint mit einem erhöhten Risiko für Arthrosen im Knie-und Hüftgelenk assoziiert zu sein [36].…”
Section: üBerlastungsschädenunclassified
“…In a systematic review and meta-analysis, Tran and associates concluded that there is very low quality evidence to support the increased relationship between sports participation and OA in elite participants [19]. Similarly, findings from the osteoarthritis initiative shows there is no increase in symptomatic knee OA among selfselected runners when compared to non-runners and running is not detrimental in people without OA knee [20].…”
Section: Osteoarthritis-its Prevalence and Predisposing Factorsmentioning
confidence: 99%